Diverse reactivity of borenium cations with >N–H compounds. Issue 57 (28th June 2016) - Devillard, Marc; Mallet-Ladeira, Sonia; Bouhadir, Ghenwa; Bourissou, Didier
Abstract : The P-stabilized borenium1 displays rich reactivity towards >N–H compounds: substitution reaction at a borenium center with Ph2 NH, Lewis adduct formation and subsequent deprotonation with NH3, B–Mes cleavage and formation of a dicationic species with HNTf2 . Abstract : The Ph2 P-stabilized borenium1 reacts cleanly with PhNH2, NH3 and HNTf2 to give a variety of boron compounds, namely the amino-substituted borenium2 (substitution reaction at B), the neutral phosphine–borane3, the mixed P/N-stabilized boronium4 and the dicationic boron species6 . Remote modulation of the Lewis acidity at boron has been studied by preparing the related iPr2 P-stabilized borenium7 and reacting it with dihydrogen.